Autocratic Leadership, Organizational Culture, and Employee Turnover Intention: Evidence from the Textile Manufacturing Industry - Ryan Andriana Putra; Yenny Maya Dora (Al-Qalam Institue, 2026)
This study examines the partial and simultaneous effects of autocratic leadership and organizational culture on employee turnover intention. A quantitative descriptive-verificative approach was employed using a survey method. Data were collected from 100 permanent employees selected through simple random sampling from a population of 133 employees. A five-point Likert scale questionnaire was used, and the data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, and an F-test. The results indicate that autocratic leadership has a positive and significant effect on turnover intention (B = 0.185; t = 3.028; p = 0.003). Organizational culture also has a positive and significant effect on turnover intention (B = 0.211; t = 3.150; p = 0.002). Both variables simultaneously have a significant effect on turnover intention (F = 17.415; p < 0.001) and explain 26.4% of its variance. These findings suggest that organizations should promote participative leadership, strengthen supervisor–employee communication, and foster a supportive organizational culture through fair rewards, career development opportunities, and collaborative work practices to reduce employees’ intention to leave.